The challenge of access to care for soft tissue sarcomas bridging pediatric and adult age: the Italian pediatric oncology view. Issue 2 (February 2012) - Ferrari, Andrea; Bisogno, Gianni; Meazza, Cristina; de Pava, Marco Vajna; Sultan, Iyad; De Salvo, Gian Luca; Clerici, Carlo Alfredo; Veneroni, Laura; Casanova, Michela
Synovial sarcoma and rhabdomyosarcoma are two high-grade soft tissue sarcoma subtypes that occur in adolescents and young adults. Managing these malignancies in patients in this age bracket poses various clinical problems, partly because different therapeutic approaches are sometimes adopted by pediatric and adult oncologists, even though they are dealing with the same condition. In this review, the doubts concerning how best to manage soft tissue sarcomas in patients between pediatric and adult ages lead up to a more general discussion of the issue of access to optimal cancer services for adolescents and young adults – a subset of patients acknowledged as being under-represented in clinical trials on therapies that may improve their outcome. The situation in Italy is described, along with action taken in an effort to bridge the gap and implement specific programs tailored to these patients.